The Role of Financial Statement Transparency in Preventing Profit Manipulation - Athaya, Nada; Safitri, Tsamara; Manao, Marcella; Panggabean, Fitri (Indonesian Journal Publisher, 2025)
This study examines the role of financial statement transparency in preventing profit manipulation practices in public companies. Financial statements serve as the primary means of communication between companies and external stakeholders, such as investors and creditors. However, profit manipulation practices, such as timing adjustments to revenue or expense recognition, are still common in many companies. Such manipulation can undermine the credibility of financial information, reduce investor confidence, and create market distortions. This study employs a descriptive qualitative approach with a literature review to explore the relationship between financial statement transparency and the reduction of profit manipulation tendencies. The results indicate that good financial statement transparency can curb profit manipulation practices by enhancing accountability and more effective internal oversight. Therefore, transparency is not merely a technical aspect of reporting but also serves as a vital control mechanism in ensuring the integrity of financial statements.